Relative intakes of tar, nicotine, and carbon monoxide from cigarettes of different yields. - Wald, N J (1984)
The relative intakes of tar, nicotine, and carbon monoxide were estimated in 2455 cigarette smokers, who freely smoked their usual brands of cigarette. The estimates were derived by using an objective index of inhaling based on the measurement of carboxyhaemoglobin divided by the carbon monoxide yield of the cigarettes smoked, after background and carry over carboxyhaemoglobin effects had been allowed for. Separate analyses were performed according to the yield and type (plain, filter, etc) of cigarette smoked. The analyses based on yield indicated that the extent of inhaling was adjusted sufficiently to achieve similar intakes of nicotine/carbon monoxide regardless of the nicotine/carbon monoxide yield. It was not, however, sufficiently increased to achieve a similar intake of tar as the tar yield of the cigarette decreased. The analyses based on type of cigarette indicated that the extent of inhaling was adjusted to achieve similar intakes of tar and nicotine regardless of the type of cigarette smoked, but that this led to a greater intake of carbon monoxide among filter cigarette smokers than that among smokers of plain cigarettes--more so than would have been expected from their relative carbon monoxide yields. Two conclusions arise from these results. Firstly, any harmful effects of nicotine/carbon monoxide are unlikely to be materially reduced by smoking cigarettes with lower yields of nicotine/carbon monoxide, but the harmful effects of tar are likely to be reduced by smoking cigarettes with lower tar yields. These predictions appear to be borne out by epidemiological observations. Secondly, any harmful effects of carbon monoxide on the cardiovascular system will be greater in smokers of modern filter cigarettes than in smokers of modern plain cigarettes, provided that these two groups of smokers are otherwise similar with respect to risk of cardiovascular disease.